Effect of Melt Temperature on the Effectiveness of the Grain Refining in Al-Si Castings - A. M. Samuel; S. S. Mohamed; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering)
The results inferred from the present work show that Al3Ti phase has a strong affinity to react with silicon (Si) in the molten alloy leading to formation of (Al,Si)3Ti phase instead. This reaction is independent of the grain refiner type. The molten liquid temperature would change its morphology from platelets at 750°C into dendritic structure at 950°C. It has also been observed that (Al,Si)3Ti phase platelets precipitate within the α-aluminum dendrites, whereas TiB2 or AlB2 particles are released into the surrounding interdendritic regions. Introduction of the grain refiner, regardless its type, would cause change in the α-aluminum dendrite morphology from an elongated to a more rounded form. The results also reveal that addition of 100 ppm B will reduce the initial grain size by ∼85% which is more than the effect of addition of 0.2%Ti in the form of Al-10%Ti (about 65%). Elimination of undercooling is important to obtain the maximum grain refining effect.